Pengaruh Return On Assets dan Efisiensi Terhadap Pertumbuhan Laba Bank Yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021 - Lailatul Nur Mufidah; Rosento Rosento (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
This research was conducted with the aim of knowing the effect of return on assets and efficiency on the profit growth of banks listed on the Indonesia Stock Exchange for the 2019-2021 years. This research was conducted with multiple linear regression analysis. The sample in this study is 20 banking companies listed on the Indonesia Stock Exchange for the 2019-2021 years so that the total sample is 60 companies. The results showed that the variable return on assets has a significant positive effect on profit growth. These results indicate that return on assets affects profit growth so that banks must always optimize the use of their assets. Furthermore, the efficiency variable proxied by BOPO has no significant effect on profit growth, this can be caused by the pandemic factor which has caused the banking profit growth rate to decrease. The results of the study found that simultaneously return on assets and efficiency have a significant effect on profit growth